Dynamic Capabilities and Competitive Advantage of International Schools in Kenya - Mulamba, Michael; Kariuki, Paul; Nguyo, Reuben (European Journal of Business and Strategic Management, 2025)
Purpose: The purpose of this study was to investigate the effect of Dynamic Capabilities on the competitive advantage of international schools in Kenya. Specifically, the study aimed to establish the influence of knowledge management capabilities, information communication technology capabilities, organizational assets and learning capabilities on the competitive advantage of international Schools in Kenya. Methodology: The research design used was descriptive survey. The target population included the 42 schools offering different international curriculum in Nairobi-County. A sample of 168 respondents was randomly selected for this study, comprising of one school principal, one Head of Section, one head of department and one senior teacher from each of the school. The researcher used questionnaires to collect primary data. Qualitative data was analyzed using descriptive statistics with aid of SPSS Version 24. The findings were presented using tables,bar graphs and pie charts. Findings: The study found that knowledge management capabilities significantly influenced the competitiveness of international schools in Kenya (r=0.877, p=0.000; β1=1.122, p=0.000). Information communication technology capabilities also had a significant positive impact on competitive advantage (r=0.705, p=0.000; β2=1.060, p=0.000). Organizational assets were positively correlated with competitive advantage (r=0.705, p=0.000; β3=0.965, p=0.000). Learning capabilities also significantly influenced competitive advantage (r=0.618, p=0.000; β4=0.877, p=0.000). Unique Contribution to Theory, Practice and Policy: The study advances dynamic capabilities theory by contextualizing it within international education, informs policy on strategic resource development for global competitiveness, and guides school leaders in enhancing adaptability, innovation, and market positioning to sustain competitive advantage in Kenya’s international school sector.